2021
DOI: 10.3390/land10020203
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Degradation of Guanshan Grassland Suppresses the Microbial Biomass and Activity of Soil

Abstract: Changes in vegetation influence the function of grassland ecosystems. A degradation of the vegetation type has been found from high to low altitudes in Guanshan grassland in the order of forest grassland (FG) < shrub grassland (SG) < herb grassland (HG). However, there is poor information regarding the effect of vegetation degradation on soil microbes in Guanshan grassland. Therefore, our study evaluated the impact of vegetation degradation on the microbial parameters of soil, as well as the mechanisms r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Our results suggest that shrubland performs better in terms of BGL, CBH, and LAP activity than meadow. This finding is supported by those of a previous study ( Liu et al, 2021 ). In addition, RHO had better soil enzyme activity than POT, which was consistent with the results of Hu et al (2016) .…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that shrubland performs better in terms of BGL, CBH, and LAP activity than meadow. This finding is supported by those of a previous study ( Liu et al, 2021 ). In addition, RHO had better soil enzyme activity than POT, which was consistent with the results of Hu et al (2016) .…”
Section: Discussionsupporting
confidence: 92%
“…It has been observed that the constant changes in the fertility of the soil occurred through various organic amendment practices [ 5 ]. Soil organic matter (SOM), characterized by the residence time and biodiversity present, regulates the movement of water by increasing the moisture-retaining capacity and provides essential nutrients for plants and microbes [ 6 ]. On the contrary, anthropic intervention with herbicides causes a decrease in the water content of the soil, which is faster in areas with less vegetation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation restoration enhances the regional ecological stability of terrestrial ecosystems and occupies an indispensable position in ecosystem C and N sinks [8,9]. Restored vegetation has been reported to alter trends in soil carbon and nitrogen sequestration and transformation of its associated pools, which is influenced by a variety of external factors, including soil characteristics (e.g., soil bulk density, pH, moisture, and temperature), climate, and type of vegetation restored [2,8,10,11].…”
Section: Introductionmentioning
confidence: 99%